NON-INVASIVE ESTHETIC REHABILITATION OF ANTERIOR DIASTEMA WITH DIRECT COMPOSITE RESTORATION - Asih Rahaju; Itoh Rositoh (Fakultas Kedokteran Gigi Unjani, 2022)
ABSTRACT Diastema is a gap between adjacent teeth that occur physiologically from the teeth eruption. However, diastema between the maxillary central incisors in an adult can be an aesthetic problem and sometimes impair speech. Diastema treatment with low or enlarged superior labial frenulum includes frenectomy, orthodontic treatment, veneers, crown, and bridge or resin-based composite direct restorations. This case report will discuss the rehabilitation of diastema in an aesthetic zone of maxillary central incisors due to low frenulum attachment. It was done by a minimally invasive approach using direct composite restoration, completed within several hours after the study model was analyzed, and much less expensive than other forms of treatment. The protocol involved model analysis, smile design, mock-up, silicon index creation, and composite selection. Patient cooperation and understanding of the limitations are critical to long-term treatment success. The direct composite resin is a fast, simple method yet durable to achieve good improvement of small diastema in the aesthetic zone. And stable after three years. DOI : 10.54052/jhds.v2n2.p329-342